2013
DOI: 10.1017/cbo9781139381277
|View full text |Cite
|
Sign up to set email alerts
|

The Political Power of Protest

Abstract: Gillion demonstrates the direct influence that political protest behavior has on Congress, the presidency and the Supreme Court, illustrating that protest is a form of democratic responsiveness that government officials have used, and continue to draw on, to implement federal policies. Focusing on racial and ethnic minority concerns, this book shows that the context of political protest has served as a signal for political preferences. As pro-minority rights behavior grew and anti-minority rights actions decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The students I interviewed suggested that social movement organizing, and subsequent social movement repression, was largely absent when they would organize on campus compared to off-campus settings. This runs counter to the findings from Gillion (2013), who argued that protests and movements grow when they are repressed and information about that repression spreads, which he called information continuum theory. Social movement scholars have a lot to gain by analyzing the unique nature of schools and universities.…”
Section: Discussionmentioning
confidence: 65%
“…The students I interviewed suggested that social movement organizing, and subsequent social movement repression, was largely absent when they would organize on campus compared to off-campus settings. This runs counter to the findings from Gillion (2013), who argued that protests and movements grow when they are repressed and information about that repression spreads, which he called information continuum theory. Social movement scholars have a lot to gain by analyzing the unique nature of schools and universities.…”
Section: Discussionmentioning
confidence: 65%
“…Minorities increase their political power when they increase their numbers in a congressional district and rally behind common goals that benefit the group. This was evident in the 1960s and 1970s as the unity of African-Americans and Latinos, and even the mutual efforts of sympathetic groups fueled the civil rights and Chicano movements and led to public policies at the local level (Gillion 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Although the link between political and/or social protest and government responsiveness has not been extensively studied as Gillion (2013) has demonstrated, collective minorities belonging to a large diversity of racial, ethnic, stigmatized, disciplinary, fragmented, and excluded identities are still struggling to gain recognition in the public sphere. Around the world, different relations between some dissenting academics and a few oppositional social movements have emerged in recent decades as a response to increased conditions of injustice.…”
Section: Always/already Acknowledging the Political: Making Mcqimentioning
confidence: 99%